The Attitudes of Canadian Ophthalmology Residents and Pre-Clerkship Medical Students at an Ontario Medical School Towards Homeless Individuals: A Cross-Sectional Study. (4th July 2021) - Sayal, Aman P.; Popovic, Marko M.; Mustafa, Majd; Hwang, Stephen W.; Lichter, Myrna
ABSTRACT: Purpose : This cross-sectional study assessed the attitudes of Canadian ophthalmology residents (PGY1-5) and pre-clerkship medical students (year 1 and 2) at the University of Toronto towards individuals experiencing homelessness. Methods : Residents and students were invited to complete the Health Professionals' Attitudes Towards the Homeless Inventory (HPATHI) tool to assess attitudes, interests and confidence in working with the homeless population on a 5-point Likert scale. Comparisons were made between residents and pre-clerkship learners and between junior and senior residents using the Fisher exact test and Mann-Whitney U test. Results : Responses were received from 114 of 220 ophthalmology residents (52%) and 315 of 534 (59%) pre-clerkship medical students. Ophthalmology residents had significantly more negative overall attitudes (pre-clerk median = 4.4, resident median = 4.1, both still indicating positive attitudes) and interests (pre-clerk median = 4.0, resident median = 3.3, residents with more neutral interests) towards working with the homeless population compared to pre-clerkship medical students. Using both statistical methods, beliefs were significantly more negative in 7 of 9 'Attitude' items, 5 of 5 'Interest' items and 1 of 4 'Confidence' items. Ophthalmology residents were only more positive in 1 of 4 of the 'Confidence' items. Attitudes were similar across PGY1-5 training years, except PGY4 and PGY5 residents were more negative than PGY1-3 residents on 1 of 5 'Interest' items. Conclusions : Ophthalmology residents have an at least neutral perception of individuals experiencing homelessness, while medical students have a more positive opinion. Studies exploring optimal ways to advocate for this population are needed for Canada's eye-care trainees.